A novel parallel image encryption with chaotic windows based on logistic map. (August 2017) - Rostami, Mohamad Javad; Shahba, Abbas; Saryazdi, Saeid; Nezamabadi-pour, Hossein
Highlights: We propose parallel plain-image-dependent encryption algorithm with chaotic windows. A float number is generated from input that update the initial values of chaotic map. The input is broken into blocks and is encrypted using XOR and chaotic windows. The proposed algorithm meets the theoretical criteria :entropy, NPCR, UACI and CC. The proposed algorithm showed high efficiency against noise and data loss attack. Abstract: Over the course of the last two decades, secure communication has become a very important issue due to the rapid growth of information technology and the development of public communication networks in which digital images are widely transmitted. In this paper, logistic map was employed for the encryption of gray-scale images. The proposed algorithm, demonstrating a proper performance according to the experimental results, divides the image into blocks and encrypts them with XOR operation and chaotic windows. Moreover, it has a large key space and the resulted encrypted images have homogeneous histograms. The large-enough NPCR and UACI of this algorithm indicate its resistance to differential attacks, not to mention the fact that it is suitable for noisy communication networks and could be made use of in parallel processing. Graphical abstract: